STABILIZATION MEASURES TO IMPROVE THE ECONOMIC AND ENVIRONMENTAL MANAGEMENT OF OIL AND GAS EXTRACTION ENTERPRISES - FADYEYEVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the necessity of implementing organizational, technological and economic measures of environmental orientation, the purpose of which is to reduce environmental damage and significant economic losses, and therefore to improve the financial condition of enterprises. The latest scientific research in the direction of solving the problems of assessing the levels of environmental danger and related environmental risks of oil and gas production enterprises is analyzed. The importance of solving economic and environmental problems of oil and gas enterprises is shown on the example of an oil and gas production enterprise. Systematized external factors of natural, man-made, social origin as sources of danger and threats to the enterprise. The sequence of formation of the mechanism for preventing the occurrence of ecologically dangerous risk-events, the purpose of which is to identify the sequence of events leading to accidents, as well as the development of scenarios for the occurrence and development of accidents and the assessment of the probability of their occurrence, is given. Stabilization measures to improve the economic and environmental management of oil and gas production enterprises are proposed. The use of the obtained research results will allow to optimize management decisions during strategic planning by comparing the specifics of the oil and gas production enterprise with strategic changes in the external environment.
Keywords: economic and environmental management; dangerous events; sources of dangers and threats; risk-event; stabilization measures